PENGARUH MEDIA CROSSWORD TERHADAP KEMAMPUAN MENULIS ANAK USIA 5-6 TAHUN DI TK MIFTAHUL ILMI KOTA PEKANBARU - Afriani, Yesi; Risma, Devi; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Based on observations that have been done by researchers on children aged 5-6 years in TK Miftahul Ilmi Pekanbaru City still found some problems writing. Such us, there are still children who are difficult to write their own names, there are still children who are difficult to imitate the letters written by teachers, there are still children who are difficult to write a few words written by teachers, there are still children who are difficult to make lines or curves as letters. This research is purposed for to know the influence using crossword media to ability of writing children aged 5-6 years in TK Miftahul Ilmi Pekanbaru City. This research is experiment research using one group design with pretest and posttest. The sample that used is 15 people in this research. File accumulation’s technique that used is observation. Technique of data analysis using t-test test by using program of SPSS 16.0. The research hypothesis is that there is a significant influence on children's writing ability after applying media crossword. To find the hypothesis accepted or rejected based on data SPSS 16.0 can be seen tcount ꞊27,191 is bigger than ttable ꞊ 2,131 (27,191> 2,131). Thus Ho is rejected and Ha accepted which means there is a significant difference between before and after doing experimentation by applying crossword media. The results of this study also see the effect of crossword media use on writing ability of children aged 5-6 years. This can be known from the influence of the use of media crossword based on calculation using Gain formula that is equal to 43.33% is in the medium category and 56.67% influenced by other factors.Key words: Writing abilty, crossword media